Peran Sumatera Thawalib dalam Pendidikan Islam di Minangkabau - Saputri, Saputri; Aurindya, Alda; Husnayan, Muhammad Hanif; Siregar, Yusra Dewi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to examine the role of the Sumatera Thawalib educational institution in the development of Islamic education in the Minangkabau region. Sumatera Thawalib was one of the significant Islamic educational organizations that played a crucial role in the dissemination and renewal of Islamic teachings as well as in shaping the character of the Minangkabau community in the early 20th century. Using a qualitative historical approach, this research collects data from various primary and secondary sources, such as archival documents, historical literature, and interviews with educational figures and local historians. The results show that Sumatera Thawalib made a significant contribution in creating a progressive and modern Islamic education system in Minangkabau. This institution not only emphasized the teaching of classical religious knowledge but also integrated general knowledge and character education in accordance with the social and cultural context of Minangkabau. Additionally, Sumatera Thawalib served as a forum for the emergence of Islamic scholars and intellectuals who played a role in renewing Islamic thought and strengthening the community’s Islamic identity. The role of Sumatera Thawalib is also evident in strengthening the network of Islamic education connecting various pesantren (Islamic boarding schools) and madrasahs in West Sumatra and surrounding areas. With innovative teaching methods and a structured organization, this institution was able to respond to the challenges of modernization while preserving traditional Islamic values. Furthermore, Sumatera Thawalib contributed to the development of social and political awareness among the Minangkabau community, particularly in the context of the independence movement and educational reform. In conclusion, Sumatera Thawalib holds a strategic role as a pioneer and driving force of Islamic education in Minangkabau, combining tradition and modernity. These findings provide important insights into the dynamics of Islamic education in Indonesia and its relevance in the development of education based on religious values and local culture. This research is expected to serve as a reference for developing contextual and forward-looking Islamic education.